3D visualization processes for recreating and studying organismal form - Duncan J. Irschick; Fredrik Christiansen; Neil Hammerschlag; Johnson Martin; Peter T. Madsen; Jeanette Wyneken; Annabelle Brooks; Adrian Gleiss; Sabrina Fossette; Cameron Siler; Tony Gamble; Frank Fish; et al. (iScience, 2022)
Summary: The study of biological form is a vital goal of evolutionary biology and functional morphology. We review an emerging set of methods that allow scientists to create and study accurate 3D models of living organisms and animate those models for biomechanical and fluid dynamic analyses. The methods for creating such models include 3D photogrammetry, laser and CT scanning, and 3D software. New multi-camera devices can be used to create accurate 3D models of living animals in the wild and captivity. New websites and virtual reality/augmented reality devices now enable the visualization and sharing of these data. We provide examples of these approaches for animals ranging from large whales to lizards and show applications for several areas: Natural history collections; body condition/scaling, bioinspired robotics, computational fluids dynamics (CFD), machine learning, and education. We provide two datasets to demonstrate the efficacy of CFD and machine learning approaches and conclude with a prospectus.